2018
DOI: 10.3390/agronomy8050075
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Aquaponic Water Use for NFT Baby-Leaf Production: Mizuna and Rocket Salad

Abstract: Aquaponics is a recirculating technology that combines aquaculture with hydroponics. It allows nutrients from fish waste to feed plants and thus saves water and nutrients. However, there is a mismatch between the nutrients provided by the fish waste and plant needs. Because of this, some nutrients, notably N, tend to accumulate in the aquaponic water (APW or AP water). The aim of this study was to investigate how APW, which is depleted of P and K but still rich in N, could be further utilized. APW was used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This aspect, as reported by several authors [3, 20, 21], reduced the effective nitrification of the ammonium produced by fish, thus slowing the N availability for the plant. During the experiment, after the full activation of the biofilter, the yield of crop, especially in the APL, was comparable or higher than the control due to the continuous supply of N compounds from the fish and probably also due to the accumulation of several humic-like and protein-like dissolved organic matter components in the water [22] that exert a biostimulant effect [23, 24]. Considering the yield values, the production of catalogna was lower (-60%) than that obtained in open-field conditions [25]; the production of lettuce, on the other hand, especially for HP and APL, is in line with that reported in other soilless experiments [26].…”
Section: Discussionmentioning
confidence: 99%
“…This aspect, as reported by several authors [3, 20, 21], reduced the effective nitrification of the ammonium produced by fish, thus slowing the N availability for the plant. During the experiment, after the full activation of the biofilter, the yield of crop, especially in the APL, was comparable or higher than the control due to the continuous supply of N compounds from the fish and probably also due to the accumulation of several humic-like and protein-like dissolved organic matter components in the water [22] that exert a biostimulant effect [23, 24]. Considering the yield values, the production of catalogna was lower (-60%) than that obtained in open-field conditions [25]; the production of lettuce, on the other hand, especially for HP and APL, is in line with that reported in other soilless experiments [26].…”
Section: Discussionmentioning
confidence: 99%
“…Delaide et al (2016) demonstrated that aquaponics production with nutrient supplementation performed better than conventional aquaponics and hydroponics. Nicoletto et al (2018) found that aquaponics water lacks adequate levels of P and K to meet desirable yields of baby leaf greens, whereas supplementation with these nutrients showed better growth of the varieties when compared to conventional hydroponics. Estrada et al (2018) proposed the use of stochastic models for predicting and analysing the production of tilapia ( Oreochromis niloticus ) and lettuce cultivated in an aquaponic system.…”
Section: Introductionmentioning
confidence: 99%
“…Schmautz et al () obtained significantly lower tomato production in NFT than in a floating raft system but not than medium‐based system (Maucieri et al, ). Nevertheless, NFT appears to be an appropriate technology for aquaponics, based on capital cost and ease of use (Goda, Essa, Hassaan, & Sharawy, ; Lennard & Leonard, ; Nicoletto et al, ).…”
Section: Introductionmentioning
confidence: 99%